12‐month primary patency rates of contemporary endovascular device therapy for femoro‐popliteal occlusive disease in 6, 024 patients: Beyond balloon angioplasty. Issue 4 (8th May 2014) - Marmagkiolis, Konstantinos; Hakeem, Abdul; Choksi, Nishit; Al‐Hawwas, Malek; Edupuganti, Mohan Mallikarjuna Rao; Leesar, Massoud A.; Cilingiroglu, Mehmet
<x xml:space="preserve">Abstract</x> Background Endovascular approach to superficial femoral artery (SFA) disease, the most common cause of symptomatic peripheral arterial disease, remains fraught with high failure rates. Newer devices including second‐generation nitinol stents, drug‐coated stents, drug‐coated balloons, covered stents, cryo‐therapy, LASER, and directional atherectomy have shown promising results. Clinical equipoise still persists regarding the optimal selection of devices, largely attributable to the different inclusion criteria, study population, length of lesions treated, definition of "patency" and "restenosis, " and follow‐up methods in the pivotal trials. Methods A prospective protocol was developed. We performed a literature search using PubMed from January 2006 to November 2013. Published articles including endovascular interventions in SFA or popliteal arteries with reported 12‐month "primary patency" or "binary restenosis" rates as endpoints were included. Results We identified 6, 024 patients in 61 trials reporting 12‐month primary patency rates in patients with femoropoliteal disease. Primary patency rates were (weighted average) 77.2% for nitinol stents, 68.8% for covered stents, 84% for drug eluting stents, 78.2% for drug eluting/coated balloon, 60.7% for cryoballoon, 51.1% for LASER atherectomy, 63.5% for directional atherectomy and 70.2% with a combination of endovascular devices. Conclusion The most frequently used endovascular devices yielded various 12‐month primary patency rates ranging from 51% to 85%. The increased variation in inclusion criteria, length, and complexity of lesions between studies does not allow direct comparison between them. Larger randomized trials in specific patient populations comparing those modalities is needed before we can make safe recommendation of the superiority of one device over the other. © 2014 Wiley Periodicals, Inc.